(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The purpose of this study was to find out the differences in sleeping patterns among agriculture students on the basis of their cardiorespiratory efficiency. One hundred female agriculture students were selected for this study from Punjab Agriculture University, Ludhiana, with the age range of 20-22 years. Selected variables of cardiorespiratory efficiency and sleeping patterns were measured by the 12-minute run/walk test developed by Cooper (1968) and with the Pittsburgh Sleep Quality Index (PSQI) (Buysse et al. 1989), respectively. As per the objective of the study, descriptive statistics and comparative statistics (ANOVA) were employed by ‘SPSS Version 23.’ The results showed that there was a significant difference in sleeping patterns among female agriculture students in the terms of their cardiorespiratory efficiency.